LEADERSHIP STRATEGIES OF THE HEAD OF THE DHIYA ULHAQ AL AZIZIYAH LUENG TEUNGOH JEUNIB IN IMPROVING THE QUALITY ISLAMIC EDUCATION (Al-Mubin, 2026)
Dayah, as traditional Islamic educational institutions in Aceh, play a strategic role in shaping the character, morals and academic knowledge of the younger generation. However, the quality of Islamic education in dayah still faces various challenges, such as limited human resources, infrastructure, operational funding, and the relevance of the curriculum to the needs of the modern era. This study aims to examine the leadership strategies employed by the management of Dayah Dhiya Ulhaq Al Aziziyah Lueng Teungoh Jeunieb in improving the quality of teaching staff, to analyse the supporting factors, and to identify the main obstacles faced. The research method used is descriptive qualitative, with data collection techniques including interviews, observation and documentation. The research subjects included the dayah’s leadership, teaching staff, and students, whilst the research object was the quality of education at the dayah. The research findings indicate that the leadership strategies of the Islamic boarding school heads are visionary, adaptive and transformational, with a focus on developing a relevant curriculum, enhancing teachers’ competencies, and empowering students to become more independent. Supporting factors include the commitment of the leadership, community support, and strong traditional Islamic values. The main constraints faced are limited funding, a lack of facilities and infrastructure, and resistance to innovation. This study concludes that effective leadership is the key to improving the quality of Islamic education in Islamic boarding schools. It is hoped that these findings will contribute to the development of Islamic educational management theory whilst also providing practical solutions for Islamic boarding schools in addressing contemporary challenges.